Antiquity and geographic distribution of cranial modification among the prehistoric groups of Fuego‐Patagonia, Chile. Issue 4 (24th August 2015) - Alfonso‐Durrruty, Marta P.; Giles, Bretton T.; Misarti, Nicole; San Roman, Manuel; Morello, Flavia
ABSTRACT: Objectives: Nineteenth and twentieth century documents testify that four ethnic groups, generally classified as terrestrial hunters or canoe nomads, inhabited Fuego‐Patagonia. Archaeologically, however, their presence and temporal depth remains unknown. This study analyzes the antiquity and geographic distribution of cranial modification, a highly visible symbol of social identity, in Fuego‐Patagonia, Chile, to assess whether it expressed ethnic affiliation. Materials and Methods: A total of 60 adult skulls from Southern Patagonia ( n = 32; 53.3%) and Tierra del Fuego ( n = 28; 46.7%) were examined for age‐at‐death, sex and cranial modification with standard methods. Individuals were further categorized as terrestrial ( n = 26; 43.3%), marine ( n = 21; 35%) or indetermined hunter‐gatherers ( n = 13; 21.7%) based on the archaeological site's characteristics, geographic location, and isotopic information. Results: Thirty percent ( n = 18) of the skulls in this study were modified, and most of the modified skulls ( n = 15) presented a tabular‐erect shape. No statistically significant differences were identified between Fuegians and Patagonians, males or females, or between the different types of adaptation and geographic locations. Discussion: Thus, this Late Holocene, widely distributed practice, was not a reflection of ethnicity, but a material expression of information circulation and the complex social relations that these small‐size groups had with one another. These results suggest that the emergence of modern ethnic identities in the region is a historic process that resulted from the interaction of local groups with European and Criollos. Am J Phys Anthropol 158:607–623, 2015. © 2015 Wiley Periodicals, Inc.